KAJIAN YURIDIS MENGENAI UPAYA HUKUM DAN AKIBAT HUKUM TERHADAP PENETAPAN TERSANGKA TANPA BUKTI YANG CUKUP - Akbar Sanjaya (Universitas Suryakancana, 2022)
Investigations are carried out by the Police in order to collect evidence of a criminal act, with the aim of finding the suspect. To prevent the suspect from escaping, the investigation is accompanied by coercive measures such as arrest and detention. The determination of the suspect violates the human rights of the reported party, for this reason, investigators are required to first collect two pieces of evidence, but what happens if the reported party is designated as a suspect without sufficient evidence. This research was conducted to find out the legal remedies that can be taken by the reported party if the police determine the reported party as a suspect without attaching sufficient evidence, and what the legal consequences will be for the complainant if the report is not proven. The type of research used is normative law by collecting legal materials in the form of file studies or reference books, articles, documents. the type of research used is normative legal research, so the approach used is the legal approach, the concept approach. The writing of this study uses primary, secondary and tertiary legal materials, the results of the study show that legal remedies that can be taken by the reported party are in the form of summoning expert witnesses when the case is held or pre-trial, this is based on positive law as a form of legal protection for the reported party written in the Act. -Law No. 8 of 1981, Regulation of the Chief of Police of the Republic of Indonesia No. 14 2012.Keywords: Confirmation of Suspect, Investigation, Legal Action